Sistema señalético turístico para museos y centros culturales de la ciudad de Ambato - Bayas Ortiz, Dayanis Eliana (2024)
The current project aims to develop a tourist signage system for museums and cultural centers in the city of Ambato under the name "Ambato Cultural Route." This proposal arises in response to the urgent need to renew the existing signage, which currently exhibits noticeable wear and lacks proper maintenance. Therefore, it is crucial to implement a guide or manual that regulates the design of new signage in these spaces, considering technical and theoretical factors related to signals, with the aim of achieving maximum effectiveness and understanding by visitors. This document addresses aesthetic aspects and delves into relevant technical and theoretical considerations to ensure optimal comprehension by visitors. The presented proposal in the project involves the application of signage supports that enhance the orientation and flow of visitors within cultural spaces, incorporating graphic elements representative of the Ambato identity. Thus, the intention is not only to facilitate navigation within cultural spaces but also to enrich the tourist experience by providing visually appealing and culturally relevant information. Through field research, necessary information was collected to contribute to the project, including interviews with relevant personnel and analysis conducted with a professional to examine the signage. In general, this project examines the signage of the spaces that constitute the "Ambato Cultural Route," aiming to standardize visual elements to consolidate a cohesive visual communication across all points of cultural interest.